Factors That Influence the Level of Farmers' Knowledge of Patchouli Cultivation Techniques in West Malangke District - Mutmainna Nurul Damri; Syafruddin; Ade Irma Surani Haliq (Tarjih : Agribusiness Development Journal, 2026)
Patchouli (Pogostemon cablin Benth.) is a strategic essential oil commodity in South Sulawesi, particularly in West Malangke District, North Luwu Regency. Despite its economic potential, many farmers still rely on traditional cultivation methods without adequate technical guidance. This study aimed to analyze the level of farmers' knowledge of patchouli cultivation techniques and to identify the factors influencing it. A quantitative survey approach was employed with 175 respondents selected through simple random sampling from a population of 1,268 patchouli farmers. Data were collected using a structured questionnaire and analyzed using Variance-Based Structural Equation Modeling (VB-SEM). Results showed that the overall level of farmers' knowledge was high (mean score = 79.48), covering technical cultivation (75.00), farm management (93.36), and post-harvest handling (70.09). Internal factors — comprising age, education level, farming experience, and training — had a significant positive effect on farmers' knowledge (T-statistic = 4.238, p = 0.000). Agricultural extension also significantly influenced farmers' knowledge (T-statistic = 2.890, p = 0.004), although extension visit frequency and duration remained low. External factors (information access, production input access, and social conditions) showed no significant direct effect (p = 0.347). The three variables collectively explained 13.7% of knowledge variability. These findings highlight the need for structured technical training programs, commodity-specific extension intensification focusing on patchouli, and prioritized improvement of post-harvest knowledge to enhance product quality and farmers' economic value.